Espécies anemocóricas no cenário de mudanças climáticas: história natural e consequências funcionais - Alves-de-Lima, Larissa (2024)
In the past 150 years, human activities such as fossil fuel burning and conversion of natural areas for agriculture and urbanization have significantly increased carbon dioxide concentrations in the atmosphere, leading to a global temperature rise of approximately 3ºC. Future projections indicate an additional increase of up to 3ºC by the end of the 21st century, with more severe impacts expected for South America, where the Cerrado region could experience temperature increases of up to 6ºC. These climate changes not only affect temperature but also alter precipitation patterns, humidity levels, and wind speeds, directly impacting biodiversity. Species face increasing risks of extinction due to physiological limitations in the face of global warming, underscoring the importance of using mathematical models to predict impacts and plan conservation strategies. Ecological niche modeling has been crucial in identifying climatically suitable areas for species survival, particularly in the Cerrado biome, one of the most biodiverse and threatened biomes in the world. In this thesis, we address these climate change impacts on Cerrado biodiversity across three chapters. Chapter 1 investigates the phenological patterns of Qualea grandiflora Mart. and Q. multiflora in response to climate variables. Chapter 2 explores the reproductive biology of Qualea multiflora, describing its floral phenology and interactions with floral visitors. Chapter 3 applies ecological niche models to predict how climate change may affect the geographical distribution of wind-dispersed species such as Aspidosperma tomentosum, Kielmeyera coriacea, Peixotoa tomentosa, Qualea multiflora, and Senna velutina in the Brazilian Cerrado.